The Meaning of the Empathetic Nurse–Patient Communication: A Qualitative Study - Atye Babaii (SAGE Publishing, 2021)
Nurse–patient communication is the foremost step in providing professional care. Nurses can use effective communication as a simple and powerful tool to create comfort, happiness, and vitality to reduce the patient's grief and suffering. This study aimed to explain the nurses’ perception of empathetic nurse–patient communication. This qualitative study was conducted with a content analysis method in 2020. Seventeen hospital nurses were recruited with maximum variation from the educational hospitals affiliated to Qom University of Medical Sciences, Qom, Iran, and semi-structured interviews were conducted until data saturation was reached. Data analysis was performed using Graneheim and Lundman approach. Nurses establish empathetic communication with patients through three main categories of: (1) having humanistic and unique behaviors with the patients; (2) providing a calm and happy environment for the patients; and (3) reducing the patients’ fear and consolation to them. These findings indicate empathetic communication that is appropriate to the conditions and needs of hospitalized patients. The three main categories were accomplished through 14 subcategories. The finding of this study can help to develop a training framework of empathetic nurse–patient communication and design instruments for measuring it.